2019
DOI: 10.7150/jca.28577
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of DACT-2 by Promoter Methylation and its Clinicopathological Significance in Prostate Cancer

Abstract: Backgrounds : Dapper homolog (DACT) 2, a member of DACT gene family, is frequently down-regulated in various malignancies and linked to tumor progression. However, the regulatory mechanism of DACT-2 expression and its biological role in human prostate cancer (PCa) remains elusive. Here, we investigated the expression and an epigenetic change of DACT-2 in prostate cancer, and determined if these findings were correlated with clinicopathologic characteristics of PCa. Methods : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…It is hypothesized that DACT-2 may be a potential tumor suppressor gene involved in tumor progression. Our previous studies have also confirmed that DACT-2 is downregulated by methylation in both prostate cancer cells and prostate cancer tissues (24). However, it is unclear whether the presence of DACT-2 gene methylation is present in the serum of patients with PCa.…”
Section: Introductionsupporting
confidence: 60%
“…It is hypothesized that DACT-2 may be a potential tumor suppressor gene involved in tumor progression. Our previous studies have also confirmed that DACT-2 is downregulated by methylation in both prostate cancer cells and prostate cancer tissues (24). However, it is unclear whether the presence of DACT-2 gene methylation is present in the serum of patients with PCa.…”
Section: Introductionsupporting
confidence: 60%
“…Previous studies have found that, the expression of DACT1 or DACT2 was reduced in various solid tumors, and was identified as a tumor suppressor genes [26,27,79]. It has been reported that DACT3 is transcriptionally inhibited and is a negative regulator of the Wnt/β-catenin signaling pathway in colorectal cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of DACT down-regulation are proved to be associated with epigenetic regulation in these tumors, including promoter methylation and histone modification. Furthermore, DACT is recognized as a tumor suppressor of Wnt/β-catenin pathway [25][26][27]. However, the role and epigenetic regulation mechanism of DACT family members are different in various tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the expression level of DACT2 was significantly reduced in primary esophageal cancer samples compared with adjacent normal esophageal mucosa, and further statistical analysis showed that the frequency of DACT2 silencing significantly correlated with differentiation and prognosis of ESCC [49][50][51]. Moreover, the decreased expression of DACT2 is closely correlated with the invasion, metastasis, occurrence, and development of gastric cancer, prostate, and papillary thyroid cancer [52][53][54][55]. Similarly, based on our findings, DACT2 was significantly down-expressed in glioma tissues compared with normal brain tissues and the paired adjacent tissues [16].…”
Section: Dact2 and Cancermentioning
confidence: 99%